BLENDED LEARNING BERBANTUAN GOOGLE CLASSROOM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK PADA MATERI KESETIMBANGAN Ion DAN pH LARUTAN PENYANGGA - Teja Pratama Putra; Maria Erna; Lenny Anwar (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2023)
The purpose of this study was to determine the improvement of students' critical thinking skills on ion equilibrium and pH buffer solution material through the application of Blended Learning assisted by Google Classroom. The research was conducted in one of the high schools in Pekanbaru City, class XI MIPA in the even semester of the 2022/2023 school year. This research is an experimental research with a research design in the form of Randomized Control Group Pretest-Posttest Design. From the existing population, there are samples in the experimental class (36 students) and the control class (33 students). The results of the research statistical test (One Tailed t-Test) show that the hypothesis is accepted with tcount 2.07> ttable 1.67 (dk = 67, α = 0.05). Indications of an increase in students' critical thinking skills due to the implementation of a combination of conventional class learning and virtual classes that build students to think more fluently, not fixated, active, creative, interactive and not bored during the learning process.